Contribuições para a otimização da programação da produção de bebidas a base de frutas - Pagliarussi, Marina Sanches (2013)
Beverage factories have been trying to improve production planning and control to increase competitive advantages and market shares. In order to achieve such goals, the industries attempted to improve the process of meeting demands, manufacture larger product variety in less time, use less resources and considering the factory´s operating limit. This work considers a production planning problem which lies in the factories which manufactures non-alcoholic beverages fruit. The research problem is the lotscheduling of drinks, characterized by: finite planning horizon, multi-period, multimachine, capacity constraints, setup time and cost, special machine constraints (the machines must be cleaned after certain production time). An optimization approach based on mathematical modeling is proposed, considering different scenarios and using optimization softwares. The proposed models are variations of mixed-integer programming models well-known in the literature, such as the GLSPPL (General Lot Sizing and Scheduling Problem for Parallel Production Lines) and CLSP (Capacitated lot sizing problem). However, instead of considering parallel machines, different arrangements of machines are considered to obtain better representation of the production processes. In order to validate the models, we proposed an approach involving a case study in a beverage factory in the state of São Paulo. The solutions obtained by the models were compared with those used in practice. The results show that the proposed approach has good potential for practical use.